2004
DOI: 10.1002/bmc.340
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the liver cytosolic proteins that bind to p‐hydroxyacetophenone

Abstract: The purpose of the present study was to determine the proteins that bind to acetophenones in the liver. Immobilized p-hydroxyacetophenone (p-HAP) was used as a ligand of affinity chromatography. Analysis using sodium dodesyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) demonstrated that five polypeptides in the liver cytosolic fraction specifically bound to the p-HAP matrix. These polypeptides were digested with Lys-specific protease and used to generate peptide maps by reversed-phase high-performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 21 publications
0
3
0
1
Order By: Relevance
“…The ability of p-HAP-Sepharose to bind glycogen phosphorylase (GP), cytosolic ALDH, adenosine kinase (AK), and class I ADH as well as glutathione S-transferase (GST)-A2, had been demonstrated previously 6) . The additional capacity of the same resin to bind PKCI and MIF in the liver is proposed in this study.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The ability of p-HAP-Sepharose to bind glycogen phosphorylase (GP), cytosolic ALDH, adenosine kinase (AK), and class I ADH as well as glutathione S-transferase (GST)-A2, had been demonstrated previously 6) . The additional capacity of the same resin to bind PKCI and MIF in the liver is proposed in this study.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, it is very important to investigate proteins that interact with p-HAP in all creatures. Previous studies have shown that the resin has multi potency to hold several proteins including alcohol dehydrogenase (ADH) and ALDH in the rat liver 6) . These enzymes mainly contribute to detoxifying alcohols.…”
Section: Introductionmentioning
confidence: 99%
“…Um bom exemplo deste efeito pode ser encontrado na cristalização da 4'-hidroxiacetofenona (HAP), também conhecida por piceol. Este é um composto com diversas aplicações comerciais, onde se inclui a produção de borrachas, plásticos, fármacos, aromas e cosméticos [17,18].…”
Section: Cristais Com Estrutura!unclassified
“…4 Previous investigation showed that several liver polypeptides in the liver cytosolic fraction specifically bounded to the p-HAP matrix suggesting the pharmacological potential for the application of p-HAP derivatives in liver diseases. 5 Meanwhile, a series of p-HAP derivatives were revealed with diverse pharmacological activities including stimulated bile secretion, lipid-lowering, 6,7 anti-inflammatory, 8 anti-cancer, 9 anti-pathogenic microorganism 10 and antipsychotics. 11 Currently, p-HAP isolated from Artemisia morrisonensis was also revealed with inhibitory activity on HBV, the mechanism of which might involve the regulation of viral surface gene expression and block virion secretion by interference with the endoplasmic reticulum (ER) stress signaling pathway.…”
mentioning
confidence: 99%